Landslide risk on photovoltaic power stations under climate change - Chae Yeon Park; Min Gyun Cho; Chan Park; Ho Gul Kim (Geomatics, Natural Hazards & Risk)
To achieve the net-zero carbon dioxide emission goals, the number of solar photovoltaic (PV) power stations (PPSs) installed worldwide has increased. An increasing number of PPSs are exposed to natural hazards, such as landslides. However, the socioeconomic impact of landslide risk on PPSs has rarely been assessed nationally. In this study, we assessed the landslide risk for PPSs by combining statistical susceptibility and physical-based hazard analyses under three representative concentration pathways (RCPs). We found that the cumulative landslide-susceptible area (LSA) during the current, 2040s, and 2090s periods could vary depending on RCP scenarios: 2895 (RCP2.6), 3417 (RCP6.0) and 5492 km2 (RCP8.5). Especially, under RCP6.0, due to the spatial match with the distribution of LSA and the PPSs, the landslide risk on PPSs could become about 60 million dollars per year. This loss would be 24 million dollars more than the risk of RCP2.6. This study provides insights into the economic loss of PPSs from landslides in the Republic of Korea and suggests that severe climate change would bring a significant increase in this economic loss, which may occur in other countries with large mountainous areas.